2021
DOI: 10.1007/s12369-020-00731-z
|View full text |Cite
|
Sign up to set email alerts
|

Female-Type Android’s Drive to Quickly Understand a User’s Concept of Preferences Stimulates Dialogue Satisfaction: Dialogue Strategies for Modeling User’s Concept of Preferences

Abstract: This research develops a conversational robot that stimulates users’ dialogue satisfaction and motivation in non-task-oriented dialogues that include opinion and/or preference exchanges. One way to improve user satisfaction and motivation is by demonstrating the robot’s ability to understand user opinions. In this paper, we explore a method that efficiently obtains the concept of user preferences: likes and dislikes. The concept is acquired by complementing a small amount of user preference data observed in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Therefore, we adopted it as a knowledge model that satisfies the requirements of both language generation and knowledge processing. In the previous study [9], it is difficult to increase the number of noun types. On the other hand, in our method using semantic networks, the number of noun types can be increased simply by creating new nodes and adding them to the existing semantic network.…”
Section: Opinion Modelmentioning
confidence: 93%
See 4 more Smart Citations
“…Therefore, we adopted it as a knowledge model that satisfies the requirements of both language generation and knowledge processing. In the previous study [9], it is difficult to increase the number of noun types. On the other hand, in our method using semantic networks, the number of noun types can be increased simply by creating new nodes and adding them to the existing semantic network.…”
Section: Opinion Modelmentioning
confidence: 93%
“…However, the opinions are limited to the same topic. In the previous study [9], it is not suggested that this method is effective even in the case of mixed topics, such as "pizza" and "cake" where it is not certain that the tendencies of opinion are the same. Hence, This study adopts semantic networks to the model user's opinion.…”
Section: Opinion Modelmentioning
confidence: 97%
See 3 more Smart Citations